Clinical implication of genetic composition and molecular mechanism on treatment strategies of HER2-positive breast cancers - Chow, Christopher Y.C.; Lie, Erich Ferdiansyah; Wu, Cheng-Hsun; Chow, Louis W.C. (Frontiers in Oncology, 2022)
The current clinical management model of HER2-positive breast cancers is commonly based on guidelines, which in turn are based on the design and outcome of clinical trials. While this model is useful to most practicing clinicians, the treatment outcome of individual patient is not certain at the start of treatment. As the understanding of the translational research of carcinogenesis and the related changes in cancer genetics and tumor microenvironment during treatment is critical in the selection of right choice of treatment to maximize the successful clinical outcome for the patient, this review article intends to discuss the latest developments in the genetic and molecular mechanisms of cancer progression and treatment resistance, and how they influence the planning of the treatment strategies of HER2-positive breast cancers.